Comparative analysis on legal regulations of domain names in the US and Uzbekistan - Jamshid Turdibekov. LL.M (PT ANTIS International Publisher, 2024)
This study examines the legal frameworks governing domain name trade, focusing on trademark integration with domain name registration processes in the United States and Uzbekistan. Analyzing current regulations, the research identifies gaps in protecting intellectual property rights, preventing cybersquatting, and ensuring fair domain name trading. Proposed solutions include linking trademark registers with domain name registration to prevent misuse, thereby enhancing legal clarity, fairness, and intellectual property protection in the digital economy. These improvements will foster trust, innovation, and economic growth in online business environments globally..